A Room All Her Own: An Aged Care Story - Dhavernas, Catherine (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2022)
The Biography Project is a research and teaching initiative that has allowed university students to assist older persons living in isolated rural communities or long-term residential care in Australia in the telling and writing of their life story. Storytelling is valuable for individuals in later life as a means of reflecting on their past, addressing past and present challenges, connecting with others, sharing invaluable insight with younger generations and acquiring a renewed sense of worth through the process. Focusing on the story of Merle, an aged care resident who for a year and a half shared her story with the author while confined to a room of her own, the article explores the specific impact of the storytelling process as it plays out for both the teller and the listener. While doing so the article suggests that life stories like Merle’s, that convey perspectives, experiences and knowledge from a time that is no longer, might have a place within and provide a worthwhile resource for the field of literary studies including the study of the spatial dimension.